The Creation of a Competent Global Regulatory Workforce - Bridges, William (Frontiers in Pharmacology, 2019)
Regulatory affairs professionals play pivotal roles in ensuring healthcare products adhere to regulations and in gaining regulatory approval for product manufacture and sales. To do this, they must understand the science and technology connected with a product, the company’s business goals, and, most importantly, the nuances of national and international regulations and guidances connected to the product. But although they perform complicated work connected to the entire product development lifecycle, surveys indicate only 14% of regulatory professionals come to the field with a degree related to the work and for more than half, regulatory work is a “second career.” The net result is a heterogeneous professional population that must learn complex, detailed work on the fly in as little time as possible. Without a structure to guide development, these expectations are a challenge for someone new to the field, that person’s supervisor, and anyone developing training for him or her. Various nonprofit groups have created competency models to provide this structure, but because competencies only identify traits demonstrated by high-performing professionals, not the specific tasks associated with individual roles, these models have had limited impact on the profession. Identifying and structuring actionable tasks based on a competency model would increase the model’s utility, dissemination, and usage. Entrustable professional activities might provide the methodology for doing so.